2006
DOI: 10.1016/j.bbadis.2005.09.008
|View full text |Cite
|
Sign up to set email alerts
|

VSL#3 probiotic preparation has the capacity to hydrolyze gliadin polypeptides responsible for Celiac Sprue probiotics and gluten intolerance

Abstract: The native structure and distribution of gliadin epitopes responsible for Celiac Sprue (CS) may be influenced by cereal food processing. This work was aimed at showing the capacity of probiotic VSL#3 to decrease the toxicity of wheat flour during long-time fermentation. VSL#3 (10(9) cfu/ml) hydrolyzed completely the alpha2-gliadin-derived epitopes 62-75 and 33-mer (750 ppm). Two-dimensional electrophoresis, immunological (R5 antibody) and mass spectrometry analyses showed an almost complete degradation of glia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
152
1
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 214 publications
(162 citation statements)
references
References 54 publications
3
152
1
6
Order By: Relevance
“…25 Intraluminal therapies of CD are based on the use of ancient variants or genetic modifications of wheat as well as the pretreatment of flour by means of sourdough fermentation using certain lactobacilli with subsequent proteolysis of gluten. 16 Our results showed that oral administration of the S. boulardii KK1 strain in the G þ mice ameliorated the clinical manifestations of coeliac-like disease induced by gluten, decreased the local production of proinflammatory cytokines and downregulated the expression of CD71, which was confined to the basolateral pole of enterocytes. KK1 treatment of the G þ mice increased COX-2 production in the small intestine, which is potentially related to processes that maintain gut mucosa integrity.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…25 Intraluminal therapies of CD are based on the use of ancient variants or genetic modifications of wheat as well as the pretreatment of flour by means of sourdough fermentation using certain lactobacilli with subsequent proteolysis of gluten. 16 Our results showed that oral administration of the S. boulardii KK1 strain in the G þ mice ameliorated the clinical manifestations of coeliac-like disease induced by gluten, decreased the local production of proinflammatory cytokines and downregulated the expression of CD71, which was confined to the basolateral pole of enterocytes. KK1 treatment of the G þ mice increased COX-2 production in the small intestine, which is potentially related to processes that maintain gut mucosa integrity.…”
Section: Discussionmentioning
confidence: 75%
“…Saccharomyces Boulardii KK1 Strain, a Presumptive Probiotic, Improves Gluten-Induced Enteropathy Because probiotics have been shown to hydrolyse gliadin in vitro, 16 we examined whether presumptive probiotics with established immunoregulatory activity 14,15 have an effect in vivo in the gluten-induced mouse model for CD. The hydrolytic activity of L. paracasei DC412, DC205 or S. boulardii KK1 strains was first verified in vitro by preparing wheat flour fermentation in the presence of these strains.…”
Section: Gluten Induces Adaptive and Innate Immunity Mediators In Thementioning
confidence: 99%
See 2 more Smart Citations
“…Prolyl peptidase activity has already been characterized in several species in the LAB family including, Lactobacillus helveticus, Lactobacillus sakei, Lactobacillus reuteri and Lactococcus lactis (Degraeve et al, 2003;Sanz et al, 2001;Rollan & Font de Valdez, 2001;Xu et al 2002). Furthermore, LABs are capable of detoxifying glutenderived peptides during food processing (Rizzelo et al 2007, De Angelis et al 2006). …”
Section: Prolyl Peptidase Activity In Probiotic Bacteriamentioning
confidence: 99%